Monitoring of cell layer coverage and differentiation with the organic electrochemical transistor1. Issue 29 (7th August 2015) - Ramuz, M.; Hama, A.; Rivnay, J.; Leleux, P.; Owens, R. M.
<x xml:space="preserve">Abstract</x> High resolution monitoring of cell layer integrity with the OECT was up until now, limited to high resistance, barrier tissue type cells. In this work, the sensitivity and versatility of the device is expanded to monitor all adherent cell types.